1998
DOI: 10.4141/p97-028
|View full text |Cite
|
Sign up to set email alerts
|

Pasture research in the UK: Present knowledge and future prospects

Abstract: Davies, A. 1998. Pasture research in the UK: present knowledge and future prospects. Can. J. Plant Sci. 78: 211-216. Pasture research in the UK has increasingly been aimed at understanding the mechanisms that underlie pasture plant responses to different managements. The need to develop agricultural systems that are both sustainable and economically viable has strengthened interest in reliable animal production from pasture and has emphasised the need to understand how white clover can best be maintained in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…We found three prominent polypeptides in white clover: one 17.3‐kDa polypeptide in stolons and roots, and two 15‐kDa polypeptides in roots which were recently identified in white clover as VSPs (Corre et al, 1996; Bouchart et al, 1998), because they are involved in N storage and mobilization during regrowth after defoliation (Corre et al, 1996) The 17.3‐kDa VSP is accumulated to a large extent during winter (Bouchart et al, 1998) In other species, it has been suggested that VSPs may play a role in cold acclimation and freezing tolerance (Cyr and Bewley, 1990) as they show a seasonal pattern of accumulation with a peak at the beginning of winter (Staswick, 1994) In our conditions, VSPs showed the same pattern during the experiment for both cultivars: an accumulation during the cold period followed by a large mobilization when temperatures increased (Table 4). However, both cultivars showed the same increase in the 17.3‐kDa VSP content of stolons despite a different cold hardening capacity.…”
Section: Discussionmentioning
confidence: 99%
“…We found three prominent polypeptides in white clover: one 17.3‐kDa polypeptide in stolons and roots, and two 15‐kDa polypeptides in roots which were recently identified in white clover as VSPs (Corre et al, 1996; Bouchart et al, 1998), because they are involved in N storage and mobilization during regrowth after defoliation (Corre et al, 1996) The 17.3‐kDa VSP is accumulated to a large extent during winter (Bouchart et al, 1998) In other species, it has been suggested that VSPs may play a role in cold acclimation and freezing tolerance (Cyr and Bewley, 1990) as they show a seasonal pattern of accumulation with a peak at the beginning of winter (Staswick, 1994) In our conditions, VSPs showed the same pattern during the experiment for both cultivars: an accumulation during the cold period followed by a large mobilization when temperatures increased (Table 4). However, both cultivars showed the same increase in the 17.3‐kDa VSP content of stolons despite a different cold hardening capacity.…”
Section: Discussionmentioning
confidence: 99%